Handbook of world Englishes - Nelson, Cecil L.; Proshina, Z. G. (Zoi͡a Grigorʹevna); Davis, Daniel R.; Kachru, Braj B.; Kachru, Yamuna (Blackwell handbooks in linguistics., 2020)
The definitive reference work on World Englishes-fully revised, expanded, and updated The Handbook of World Englishes is a collection of articles on the cross-cultural and transnational linguistic convergence and change of the English language. Now in its second edition, this Handbook brings together multiple theoretical, contextual, and ideological perspectives, and offers new interpretations of the changing identities of world Englishes (WE) speakers and examines the current state of the English language across the world. Thematically integrated contributions from leading scholars and researchers explore the expansion, modification, and adaptation of English in various settings and discuss the role of English in local, regional, and global contexts. This highly regarded text has been fully updated throughout the new edition to reflect the current conditions, contexts, and functions of major varieties of English across the world. Significant revisions to topics-such as an overview of the varieties of modern world Englishes and the First Diaspora in Wales and Ireland-reflect expanded scholarship in the field and new directions of research. Each chapter from the first edition has been updated in content and citations, while 11 new chapters cover subjects including world Englishes testing and Postcolonial theory, as well as world Englishes in South America, Russia, Africa, China, Southeast Asia, the United States, and Canada. Examines both traditional and contemporary perspectives on World Englishes Written by international authors, experts in their respective fields Emphasizes the historical development of the English language through a series of diasporas Highlights research into a wide range of sociolinguistic contexts and processes including code switching, newly established WE varieties, and new data on Chinese and Russian Englishes Explores future directions in WE research, development, and application The Handbook of World Englishes is an essential resource for academics, researchers, practitioners, and advanced students in fields including applied linguistics, language teaching, the history of the English language, world literatures, and related social and language sciences.